Why do children with autism spectrum disorder have abnormal visual perception? - Zhou, Rongyi; Xie, Xinyue; Wang, Jiaojiao; Ma, Bingxiang; Hao, Xin (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is associated with severe impairment in social functioning. Visual information processing provides nonverbal cues that support social interactions. ASD children exhibit abnormalities in visual orientation, continuous visual exploration, and visual-spatial perception, causing social dysfunction, and mechanisms underlying these abnormalities remain unclear. Transmission of visual information depends on the retina-lateral geniculate nucleus–visual cortex pathway. In ASD, developmental abnormalities occur in rapid expansion of the visual cortex surface area with constant thickness during early life, causing abnormal transmission of the peak of the visual evoked potential (P100). We hypothesized that abnormal visual perception in ASD are related to the abnormal visual information transmission and abnormal development of visual cortex in early life, what’s more, explored the mechanisms of abnormal visual symptoms to provide suggestions for future research.